Pengembangan media pembelajaran matematika berbasis website dengan masalah kontekstual - Sari, Melati Puspita; Kustiawati, Dedek; Hafiz, M. (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
Contextual problem solving skills are very important for students to master. However, many students still have difficulty in problem solving. Therefore, media development is needed that can improve these skills, one of which is through website development. The purpose of this study is to develop a website as a mathematics learning media that raises contextual problems for junior high school/Islamic junior high school levels. This development research uses the Research and Development (RD) method. The methods used to collect data are observation, interviews and documentation studies for initial data collection, questionnaires for assessing the feasibility of the developed media, and evaluation tests for effectiveness tests. The subjects of this study consisted of 4 material experts, 3 Indonesian language experts, and 5 media experts. This study obtained very valid results in terms of material with a value of 95.14%. In terms of Indonesian, the results were very good with a value of 88.64%. Meanwhile, in the media test, the results were very good with a value of 93.47%. Student assessments in the initial trial stage obtained very good results of 79.92%. Student assessments in the field trial obtained very good results of 82.76%. Student assessment on dissemination got very good results of 82.82% and the effectiveness test on website-based mathematics learning media with contextual problems got good results of 77.01%. For other researchers who focus on the development of learning media, especially those based on websites, it is necessary to develop the security of the website being developed by validating the registered email.